Isolated tuberculous epididymo-orchitis masquerading as testicular tumor: a diagnostic dilemma - Rana, Shweta; Kalhan, Shivani; Satarkar, Rahul N.; Garg, Shilpa; Sangwaiya, Ashok (International Journal of Research in Medical Sciences, 2017)
Isolated tuberculous epididymo-orchitis is rare and may present with clinical and radiological features similar to those of testicular tumor. It is thus a diagnostic and therapeutic challenge. A 40 yrs old male presented with left sided mass in scrotum for past 6 months, which was clinically and radiologically diagnosed as testicular tumor with hydrocele. FNAC was attempted twice but was inconclusive. Left sided orchiectomy was done. However, the histopathological findings of testicular mass revealed features consistent with tuberculous epididymo- orchitis (TEO). This case emphasizes that patient may present with isolated TEO, which is considered an unusual presentation of tuberculosis and can masquerade as testicular tumor clinically and radiologically. But in countries where prevalence of tuberculosis is high, tuberculous orchitis must be considered in the differential diagnosis of testicular swellings.